2020
DOI: 10.1186/s12970-020-00397-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of resistance training with or without peanut protein supplementation on skeletal muscle and strength adaptations in older individuals

Abstract: Several studies suggest resistance training (RT) while supplementing with various protein supplements can enhance strength and muscle mass in older individuals. However, to date, no study has examined the effects of RT with a peanut protein powder (PP) supplement on these outcomes. Herein, 39 older, untrained individuals (n = 17 female, n = 22 male; age = 58.6 ± 8.0 years; body mass index =28.7 ± 5.8) completed a 6-week (n = 22) or 10-week (n = 17) RT program, where full-body training was implemented twice wee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…The authors suggested this was due to either an increase in connective tissue density and/or an increase in contractile protein density. We have also observed that pQCT-derived muscle density significantly increases in older participants following 6-10 weeks of resistance training [22], and explained our data in a similar fashion. One manner to view data from the current study is that inferences made from the pQCT are limited given that our histology and electrophoresis data indicated no change in myofibril density occurred with training.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The authors suggested this was due to either an increase in connective tissue density and/or an increase in contractile protein density. We have also observed that pQCT-derived muscle density significantly increases in older participants following 6-10 weeks of resistance training [22], and explained our data in a similar fashion. One manner to view data from the current study is that inferences made from the pQCT are limited given that our histology and electrophoresis data indicated no change in myofibril density occurred with training.…”
Section: Discussionsupporting
confidence: 79%
“…Biochemical methods that have been used to indirectly assess myofibril and mitochondrial densities were also performed to examine: i) if these variables were altered with training, and ii) if data yielded from these techniques were associated with data generated through phalloidin-actin staining and TOMM20 IHC. Finally, the radiological density of the vastus lateralis muscle was obtained prior to and following training and compared to data yielded from the aforementioned techniques given that this metric has been suggested to largely represent myofibril protein density of muscle tissue [6,21,22]. Based on some of the prior literature, we hypothesized that: i) areas occupied by myofibrils and mitochondria would disproportionately change relative to changes in fiber area (i.e., muscle fibers would demonstrate sarcoplasmic hypertrophy, ii) indirect measures (i.e., relative myosin heavy chain abundance and CS activity levels) would not be significantly associated with histological variables, and iii) training-induced changes in pQCT-determined muscle density would not be significantly associated with changes in muscle fiber myofibril areas.…”
Section: Introductionmentioning
confidence: 99%
“…The training program for older males has been previously described. 23 Briefly, participants underwent supervised RT twice weekly, on non-consecutive days, for six weeks. Each session consisted of five exercises including leg press, leg extensions, lying leg curls, barbell bench press, and cable pull downs.…”
Section: Rt Program For Older Participantsmentioning
confidence: 99%
“…A complete description of the testing procedures can be found in Lamb et al [20]. Briefly, participants reported to the laboratory following an overnight fast, body mass and height were assessed, and images were captured from the right leg VL using real-time B-mode ultrasonography (LOGIQ S7 Expert, GE Healthcare, USA).…”
Section: Testing Sessionsmentioning
confidence: 99%